INTEGRATION OF POWTOON LEARNING MEDIA WITH THE RESPONSIBILITY OF STUDENTS IN THE GEN Z ERA - Kadhapy, Moh.; paputungan, frezy; B. Jassin, Iwan (JCI Publisher, 2025)
Digitalization in education continues to increase, particularly in the use of learning media. However, various challenges associated with the emergence of eras based on birth years often lead to differing perspectives on improving the quality of education today. The process of integrating Powtoon learning media with a sense of responsibility in Gen Z students requires a comprehensive effort, considering that the assessment indicators for this attitude are crucial for learners in the modern era. Gen Z students (born 1997-2012) are digital natives who are pragmatic, creative, and highly dependent on technology for learning and personal branding. They favor visual-interactive methods, care about mental health/the environment, and focus on practical career outcomes (side hustles), but are prone to distraction and anxiety. Meanwhile, types of student attitude assessments generally include direct observation by lecturers, self-assessment, peer assessment, and daily journal entries. Aspects assessed include discipline, responsibility, honesty, cooperation, politeness, and initiative. This technique often uses a Likert scale or descriptive rubric. Therefore, it is crucial to pay attention to these items in the learning process at university. Powtoon is a web-based online animation and presentation creation platform that allows users to create engaging visual content, such as explainer videos, without requiring advanced graphic design skills. This application uses drag-and-drop features, ready-to-use templates, animated characters, and is supported by AI-based tools. This research uses a descriptive method, namely a research approach that aims to describe, explain, or map the characteristics of a phenomenon, situation, or population systematically, factually, and accurately based on data collected during the study. The results show the successful integration of Powtoon learning media with the responsible attitude of Gen Z students, evidenced by the existence of an orderly, understandable learning process and a high quality of understanding.